The Impact of Coffee Shops on Aceh's Economic Sustainability - Jhond Paull (Winaya Inspirasi Nusantara Foundation, 2024)
The effect of coffee shops on Aceh, Indonesia's ability to sustain its economy is examined in this article. The research is predicated on the idea that coffee, especially Arabica coffee, is a valuable product in Aceh that boosts the local economy and the income of coffee producers. The study's objectives are to examine the traits of coffee shop patrons, the variables that affect the volume of business and revenue of well-known coffee shops in Banda Aceh City, as well as the profitability of these establishments. Based on data analysis from well-known coffee shops in the area, the research design examines variables that affect both visitor volume and profit margins. The results show that young people with particular spending habits and visitation patterns frequent coffee shops. The ramifications of these discoveries for the region's economic sustainability are explored in detail, with a focus on the coffee sector. The article's conclusion highlights the importance of coffee shops to Aceh's economy as well as the need for more study and advancement in this field.